Structure-Based Screening of Plasmodium berghei Glutathione S-Transferase Identifies CB-27 as a Novel Antiplasmodial Compound - Colón-Lorenzo, Emilee E.; Colón-López, Daisy D.; Vega-Rodríguez, Joel; Dupin, Alice; Fidock, David A.; Baerga-Ortiz, Abel; Ortiz, José G.; Bosch, Jürgen; Serrano, Adelfa E. (Frontiers in Pharmacology, 2020)
Plasmodium falciparum parasites are increasingly drug-resistant, requiring the search for novel antimalarials with distinct modes of action. Enzymes in the glutathione pathway, including glutathione S-transferase, show promise as novel antimalarial targets. This study aims to better understand the biological function of Plasmodium glutathione S-transferase, assess its potential as a drug target, and identify novel antiplasmodial compounds using the rodent model P. berghei. By using reverse genetics, we provided evidence that glutathione S-transferase is essential for survival of P. berghei intra-erythrocytic stages and is a valid target for drug development. A structural model of the P. berghei glutathione S-transferase (PbGST) protein was generated and used in a structure-based screening of 900,000 compounds from the ChemBridge Hit2Lead library. Forty compounds were identified as potential inhibitors and analyzed in parasite in vitro drug susceptibility assays. One compound, CB-27, exhibited antiplasmodial activity with an EC50 of 0.5 µM toward P. berghei and 0.9 µM toward P. falciparum multidrug-resistant Dd2 clone B2 parasites. Moreover, CB-27 showed a concentration-dependent inhibition of the PbGST enzyme without inhibiting the human ortholog. A shape similarity screening using CB-27 as query resulted in the identification of 24 novel chemical scaffolds, with six of them showing antiplasmodial activity ranging from EC50 of 0.6 – 4.9 µM. Pharmacokinetic and toxicity predictions suggest that the lead compounds have drug-likeness properties. The antiplasmodial potency, the absence of hemolytic activity, and the predicted drug-likeness properties position these compounds for lead optimization and further development as antimalarials.